Pengembangan Media Interaktif Pada Materi Peredaran Darah Menggunakan Metode ADDIE - Charmelita, Pauelina; Bata, Julius; W Pandjaitan, MM Lanny (Jurnal Elektro, 2022)
The subject of Natural Sciences plays a crucial role in Elementary School Education. One of the topics covered in elementary school Natural Sciences is the circulatory system. The topic of the circulatory system in Natural Sciences can be studied extensively, particularly focusing on the closed or double circulatory system. The circulatory system is one of the challenging topics for elementary school students to understand and absorb, especially in Grade V. Some elementary school students may also struggle to comprehend the structure of the circulatory system in humans, particularly the cardiovascular system from the top or bottom. There are many tools that assist students in learning a particular subject. One useful tool for learning Natural Sciences is interactive media. This research involves the development of interactive media using the ADDIE method (Analysis, Design, Development, Implementation, and Evaluation). This paper explains the ongoing development process.